Cloud Computing Security: Assured Deletion - Ahmed, Sarmad Mahmmod; Mahmood, Baban Ahmed (Informatica, 2024)
ABSTRACT: With the advent of cloud computing, many organizations, institutions, and individuals have chosen to store their data in the cloud as a way to compensate for limited local storage capabilities and reduce expenses. However, the process of uploading data to the cloud results in relinquishing control over it, leaving the data owner unaware of the details of its storage and location. Hence, ensuring data confidentiality and integrity has emerged as a critical concern, especially with regard to cloud employees and other potential attacks. A significant amount of investigation has been conducted on the security aspects of cloud computing, with a particular focus on permanent removals. Hence, our research proposes a security system that addresses cloud-related concerns by using two distinct cloud platforms, cryptographic key partitioning, cryptographic-based random writing, and link deletion in cases of confirmed deletion. Experimental results